Feeding Lactobacilli as probiotic and proportion of Escherichia coli in the intestine of calves (Bangladesh Veterinarian, 2010)
A study was conducted to determine the ability of oral Lactobacillus bacteria as probiotic to increase the Lactobacilli and decrease the Escherichia coli (E. coli) population in the intestine of calves. Bacteria were isolated from yoghurt (Dahi) with selective de Man, Rogosa and Sharpe (MRS) agar media and identified as Lactobacillus, followed by mass production of bacterial cells and freeze drying. Four one-day-old calves were divided into two groups. One group (n=2) was fed freeze-dried bacterial cells and remaining group (n=2) was a control. After 60 days, one calf from each group was slaughtered to enumerate Lactobacillus and E. coli bacteria on intestinal wall. The number of colony-forming units (cfu) of Lactobacillus was significantly (p>0.01) higher in the intestinal wall of Lactobacillus-fed calf than in the control. On the other hand the number of E. coli was significantly (p>0.01) lower in Lactobacillus-fed calf. DOI: 10.3329/bvet.v26i1.4627 Bangl. vet. 2009. Vol. 26, No. 1, 17-22